Applying Circular Economy Principles to Urban Housing. Issue 5 (November 2020) - Marchesi, M; Tweed, C; Gerber, D
Abstract: This research seeks to develop a step change to the way housing is designed for cities in the UK. Housing demand in cities is predicted to increase. Urban centres are struggling to provide affordable housing. Moreover, cities are wasteful in terms of resource consumption, and waste generation heavily affecting the environment. The circular economy offers new ways to design, make and use houses to address these issues systemically as long as technical innovation is combined with social innovation. To date, the circular economy has mainly focused on technical innovation with limited emphasis on user social practices and behaviours. The combination of technological and social innovations through design has just appeared in emerging research and practice areas of design for sustainability. So, approaches that support the design of integrated solutions for transforming large socio-technical systems like cities are not yet well-established. To contribute to the development of integrated approaches for implementing a circular economy in urban housing, this study reviews a set of existing cases of social innovation for regenerative and restorative urban systems. Through empirical observation, we seek to integrate existing theories and concepts on circular economy and formulate theoretical insights for promoting the development of social-technical innovations.